Pendidikan Karakter di Madrasah Berbasis Pesantren: Analisis Implementasi dan Evaluasi - Rofiq, Muhammad Husnur; Fahmi, Qoriatul; Rokhman, Mauhibur; Khamim, Nur (Institut Agama Islam Daruttaqwa Gresik, 2024)
This study examines the implementation of boarding school-based character education at MTs Salafiyah Syafi'iyah Tebuireng Jombang. The moral and character degradation among students in Indonesia has reached an alarming level, necessitating systematic efforts to address it. Character education plays a crucial role in shaping a young generation that is not only academically intelligent but also morally upright. The purpose of this research is to analyze the implementation of character education based on the Islamic boarding school model at MTs Salafiyah Syafi'iyah Tebuireng and to identify the strategies and methods employed. This research uses a qualitative approach with a case study design. Data were collected through observation, interviews, and documentation. Data analysis followed the framework of data reduction, data display, and conclusion drawing as proposed by Miles and Huberman. The findings reveal that the implementation of boarding school-based character education at MTs Salafiyah Syafi'iyah Tebuireng Jombang is carried out through three main stages: planning, implementation, and evaluation. In the planning stage, the school refers to character education guidelines issued by the Ministry of Education and Culture and integrates character values into the curriculum. During the implementation stage, character education is delivered through direct instruction, exemplary behavior, and habituation. At the evaluation stage, the school uses assessment methods that actively involve student participation.